Karakteristik Ibu Hamil Berhubungan dengan Pengetahuan dalam Penggunaan Kontrasepsi Pasca Persalinan (Politeknik Kesehatan Kemenkes Mamuju, 2020)
Pregnancy is a maturation crisis that can be stressful. The maturation crisis can be overcome if the mother is ready to enter a new phase where she is ready to take on the responsibilities of being a parent and a new role so that the mother must take care of her health to prevent complications of pregnancy. Pregnancy complications can be prevented by maintaining the distance of pregnancy between one child with another child through postpartum contraception. The study aimed to determine the characteristics of pregnant women who have sufficient and good knowledge of the use of postpartum contraception. Quantitative research with an exploratory descriptive approach has been carried out on 34 pregnant women who performed antenatal care at the Kedung 2 Jepara Public Health Center. The data collection tool uses a questionnaire. Data were analyzed by univariate analysis using frequency distribution and bivariate analysis using test chi-square. The results showed that the average age of pregnant women was 29 years. The majority of pregnant women had the last high school education, work, and the average income was Rp. 1,500,000/month. The majority of pregnant women had one child and when data were collected for pregnant women who were 1st and 2nd pregnant status. The majority of pregnant women had a good level of knowledge about the use of postpartum injection contraception. The results of the chi-square test analysis showed that the characteristics of pregnant women that had a significant relationship with knowledge about the use of postpartum contraception were age (p = 0.027), education (p = 0.004), occupation (p = 0.002), number of children (p = 0.006). Meanwhile, income did not have a significant relation with maternal knowledge in using postpartum contraception (p = 0.923).